2016
DOI: 10.1371/journal.pone.0155126
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Circulating Tumor Cells in Metastatic Colorectal Cancer by the Combination of the CellSearch® System and the AdnaTest®

Abstract: Colorectal cancer (CRC) is one of the major causes of cancer-related death and reliable blood-based prognostic biomarkers are urgently needed. The enumeration and molecular characterization of circulating tumor cells (CTCs) has gained increasing interest in clinical practice. CTC detection by CellSearch® has already been correlated to an unfavorable outcome in metastatic CRC. However, the CTC detection rate in mCRC disease is low compared to other tumor entities. Thus, the use of alternative (or supplementary)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 42 publications
(46 reference statements)
4
41
0
1
Order By: Relevance
“…Firstly, CTCs that did not express EpCAM may have been excluded. EpCAM expression on CTCs has been debated, as cancer cells that undergo EMT lose EpCAM expression on the cell surface (12,21). Using flow cytometry, we have observed that the lung cancer PC-9 and H358 cell lines express EpCAM (unpublished data).…”
Section: Discussionmentioning
confidence: 92%
“…Firstly, CTCs that did not express EpCAM may have been excluded. EpCAM expression on CTCs has been debated, as cancer cells that undergo EMT lose EpCAM expression on the cell surface (12,21). Using flow cytometry, we have observed that the lung cancer PC-9 and H358 cell lines express EpCAM (unpublished data).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, CTCs are barely detectable using this system in patients with non-mCRC (10). Gorges et al (19) identified CTCs using the CellSearch ® technology and/or the AdnaTest in parallel, and demonstrated that a combined analysis with both methods leads to an elevated rate of CTC detection in patients with mCRC (positive rate, 33% for CellSearch ® ; 30% for the AdnaTest;…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why CellSearch® and TRC methods generate much lower yields of CTC than expected. As reported previously, only 30–40% of CRC patients harbor three or more CTC per 7.5 mL of blood using the immunomagnetic CellSearch® detection system (Gorges et al ., ), and only 60% of CRC patients were shown to be positive in the CTC test with blood samples using the TRC method (Sato et al ., ). Therefore, a combined analysis of more than one gene could improve the sensitivity of CTC detection by increasing the range of CTC markers, giving an important advantage in view of the well‐known phenotypic heterogeneity of CTC.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies have been performed at the time of diagnosis or during initial therapy prior to disease progression using CellSearchÒ (EpCAM antigen-based) and Transcription-Reverse Transcription Concerted Reaction (TRC, CEA mRNA-based) methods. These methods have provided useful information on CRC patients (Gorges et al, 2016;Sato et al, 2012). However, due to the heterogeneity of CTC, single antigens alone, such as EpCAM or CEA, are not sufficient to capture all the CTC in blood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation